Cultura, trabalho e conflitos em Ipatinga nos anos 60 - Souza, Paulo Roberto de (2007)
Analyzing the trajectory of life of workers searched for Arraial de Ipatinga , in the 1960 s, aiming to get a new alternative of survival, implies to deepen in a universe of information, fights and emergent contradictions of the difficulties found for them in that space. This project has as an objective to understand Ipatinga laboring class formation, as well as the undertaken work in those people routine that were expected to build their dreams from such Eldorado that did not exist, without giving a final enlightenment to all the subjects related in these pages, however. It also implies in clarifying the social issues consequences of their migration and giving visibility to the conflicts, to the emergent culture and marks left by those agents while constructing local history. The work induces to understand the power relations that had emerged from Eldorado construction, whose results in those early years were Ipatinga slaughter, in which dozens of workers had lost their lives, although the official speech informs that only seven ones had died. Considering it the biggest social conflict the marks left were registered in those people memory, it had been essential to build their society that emerged from this chaos and in this field, took place such briefing. Launching a light torch on the events constructed and reconstructed from that episode that is extend such search looking for the expectancy to infer as it gave the dispute for social control on mono-industry part, as well as the expectations run away to their clutch, through several resistance forms created by those laborers, including the politician power dispute. Moreover, the project appears in many ways, it has as main purpose to understand their geographic space as a tension place and set up visibility too many troubles caused by the actions through the time, whose contents certainly will present new challenging projects to be studied around this wide source of researches.